Patterns and drivers of recent disturbances across the temperate forest biome - Andreas Sommerfeld (Nature Portfolio, 2018)
Climate change may impact forest disturbances, though local variability is high. Here, Sommerfeld et al. show that disturbance patterns across the temperate biome vary with agents and tree traits, yet large disturbances are consistently linked to warmer and drier than average conditions.